Improved osteosarcoma survival with addition of mifamurtide to conventional chemotherapy – Observational prospective single institution analysis - Peter Múdry; Michal Kýr; Ondřej Rohleder; Michal Mahdal; Iva Staniczková Zambo; Marta Ježová; Tomáš Tomáš; Jaroslav Štěrba (Journal of Bone Oncology, 2021)
Purpose: Conventional osteosarcoma is an orphan disease. Current treatment approaches include combining a three drug chemotherapy schedule and surgery. The 3- and 5-year event-free survival (EFS) in localized disease is roughly 65 and 60%, respectively. The registration study of mifamurtide reported survival benefit, but some methodological controversies have been insufficient for FDA market authorization in contrast to EMA. Methods: prospective single centre survival analysis of a mifamurtide addition to conventional therapy in 23 patients over a 5.5 year enrolment period is reported and compared to a historical control of 26 patient with localized disease. Bias arising from observational methodology was addressed using Landmark analysis and time-dependent Cox models. Blood count dynamics were analysed during the treatment. Results: The adverse event profile was as expected with no dose limiting toxicities. There were no local relapses observed, one patient died in the first complete remission due to doxorubicin cardiotoxicity, one patient had pulmonary metastatic relapse. The observed 3- and 5-year EFS was 87.4% (CI 72.4–100%) and 87.4% (CI 72.4–100%), progression free survival (PFS) was 92.9% (CI 80.3–100%) and 92.9% (CI 80.3–100%), overall survival was 94.1% (CI 83.6–100) and 80.7% (CI 58.3–100), respectively. Comparison to the historical control showed statistically significant better PFS for mifamurtide patients (Landmark analysis; p = 0.044). Risk of progression was 5-times lower for the mifamurtide group (Cox model; HR 0.21, p = 0.136). Only subtle differences in lymphocyte counts were observed across treatment. Conclusion: the PFS benefit of mifamurtide is reported herein. The addition of mifamurtide could be considered as a best treatment option for localized osteosarcoma.